Helen Morse interviewed by Ray Edmondson, K. Foley and Andrew Pike - Morse, Helen, 1946-; Edmondson, Ray, 1943-; Foley K.; Pike, Andrew, 1946- (1976)
Morse discusses her stage and film career, particularly the films "Stone" and "Picnic at Hanging Rock".
Recorded on May 14, 1976.
Digital master available
Helen Morse, actress, at age 29 is one of Australia's leading actresses. She trained at N.I.D.A. and after a few years on the stage became involved in films and television. Her more important films include Stone, Picnic at Hanging Rock & Caddie. She is married to film producer Sandy Harbutt.
Draft uncorrected transcript available.
Keywords: Morse, Helen, -- 1947- -- Interviews; Picnic at Hanging Rock (Motion picture); Stone (Motion picture); Actors -- Australia -- Interviews